The Investigation of Translation Techniques of Students at The Fifth Semester In Translating Hortatory Exposition Text at Hkbp Nommensen University Medan - Manalu, Rimma Rosvita; Simarmata, Rina; Pakpahan, Carolina (Jurnal Kajian Ilmu Pendidikan (JKIP), 2025)
Translation techniques are a way that the translators used to get the equivalence in the level of words and phrases. In other words, translation techniques play in the level words. It based on the linguistics point of view. In this research the writer method used qualitative research. This study aims to describe students translation techniques of students in translating hortatory exposition text and to know what the dominant translation techniques that uses by student in translating hortatory exposition text. Data show bellow were analyzed the translation techniques that they use in translating hortatory exposition text. There 10 students who have been translating text. In the process of translated the text , the writer found that students use some techniques of translation techniques and classificate it each other. Based on the research finding on this study, literal translation technique is the most dominantly used in translating hortatory exposition text. So, the translation technique that most dominantly used to translate the hortatory exposition text is literature.